The Social and Emotional Impact of Fathers' Inaction on Child Rearing - Faraswati, Elsie; Fatin Nabilla R; Novi Fitria (Inovan Publisher, 2025)
The family is a crucial environment for a child's education. The role of parents, especially fathers, is crucial in supporting a child's academic achievement. Fatherlessness can negatively impact a child's psychological and academic development. The article found that fatherlessness has a significant negative impact on adolescents' academic achievement. Children experiencing fatherlessness exhibit poorer cognitive performance, lower test scores, and lower school attendance. Fatherlessness can have a detrimental impact on adolescents' academic achievement. Comprehensive interventions are needed to address the impact of fatherlessness and support children in achieving their academic potential.